Terapi Stimulasi Persepsi Signifikan Menurunkan Kecemasan Lansia - Pardosi, Sariman; Nugroho, Nehru; Donsu, Jenita DT; Ekwantini, Rosa Delima (JURNAL KEPERAWATAN RAFLESIA, 2024)
The psychological condition of a person who is full of fear and worry about something that is not certain will happen. Anxiety is a description of excessive worry accompanied by responses in the form of behavioral, cognitive, affective, psychological and physiological changes. The aim of the research was to determine the impact of perceptual stimulation group activity therapy to reduce anxiety in the elderly. The research design is a quasi experiment with a pre-post test with control group design. The sampling technique was quota sampling with a total of 60 respondents, consisting of 30 intervention group respondents and 30 control group respondents. The intervention group was given perception stimulation group activity therapy for 3 days, while the control group was given deep breathing therapy for 3 days. This research instrument uses the Hamilton Anxiety Rating Scale (HARS) questionnaire. Normality test results with a value of 0.0001 ? 0.05 data are not normal, so a non-parametric test with Wilcoxon is carried out and continued with the Mann-Whitney statistical test. The statistical test results obtained a p-value of 0.000 (